Factors Influencing Bank Profitability: A Study of Indonesian Commercial Banks - Laurencia Meidi; Tannia Tannia (Petra International Journal of Business Studies, 2025)
This study aims to analyze the effect of Capital Adequacy Ratio (CAR), Net Interest Margin (NIM), Non-Performing Loan (NPL), and Loan to Deposit Ratio (LDR) on Return on Asset (ROA) at Go Public Commercial Banks listed on the Indonesia Stock Exchange during the period 2020 to 2023. The method employed in this research is a purposive sampling technique, utilizing secondary data from the official website of the Indonesia Stock Exchange (IDX) and a quantitative approach. This research was conducted by collecting all secondary data, such as financial data from each sample, to be processed and analyzed. Hypothesis testing uses panel data regression analysis using SPSS version 30. Based on the research findings, CAR and LDR have no significant effect on ROA, while NIM and NPL exhibit a substantial impact on ROA. Strong CAR does not always guarantee bank profitability, as high cost of funds can still burden operational performance. LDR does not affect ROA, as profitability depends more on credit quality than credit volume. Poor credit assessment increases risk, limiting LDR's impact. Higher NIM indicates greater interest income from productive assets, leading to increased bank profitability. A high NPL ratio indicates poor credit quality and potential operational losses, which in turn lowers the return on assets (ROA). Therefore, maintaining a low NPL is essential.